Recurrent acute kıdney ınjury due to thrombosıs of the vena cava ınferıor - DEMİRCİ BODUR, ECE; YILDIZ, NURDAN; TRUE, ÖMER; ALPAY, HARİKA; GÖKCE, İBRAHİM (My University, 2022)
Rationale: Acute kidney injury (AKI) is a frequent complication after liver transplantation. In some patients, prompt intervention targeted at a specific etiology is of paramount importance.Presenting concerns of the patients: A 25 years old man with advanced liver cirrhosis caused by sclerosing cholangitis and autoimmune hepatitis underwent orthotopic liver transplantation. One month after surgery, severe AKI developed in conjunction with recurrent ascites and lower extremity edema. Notable clinical findings included a persistently low urinary sodium excretion, a bland urinary sediment, and an abnormally monophasic hepatic vein waveform on Doppler ultrasound.Diagnoses: Inferior vena cava stenosis.Interventions: Angioplasty with stent installation.Outcomes: Rapid improvement of renal function after stent installation.Lessons learned: The following case illustrates the importance of integrating clinical cues, ultrasound features, and laboratory findings. The combination of AKI associated with lower extremity edema, abnormal monophasic hepatic vein flow on Doppler ultrasound, and a low urinary sodium excretion after liver transplantation should evoke the possibility of inferior vena cava stenosis as the etiologic factor.

Fondement: L’insuffisance rénale aiguë (IRA) est une complication survenant fréquemment à la suite d’une greffe hépatique. Pour certains patients, une intervention rapide et ciblée sur l’étiologie spécifique s’avère d’une importance capitale.Présentation du cas: Un homme âgé de 25 ans atteint d’une cirrhose hépatique avancée causée par une cholangite sclérosante et une hépatite auto-immune a subi une greffe hépatique orthotopique. Un mois après l’intervention, le patient a développé une sévère IRA conjointement à des ascites récurrentes et un œdème des membres inférieurs. Parmi les principales manifestations cliniques figuraient la persistance d’une faible excrétion urinaire du sodium, la présence de sédiments urinaires neutres et une forme d’onde anormalement monophasique pour la veine hépatique à l’échographie Doppler.Diagnostic: Sténose de la veine cave inférieureIntervention: Angioplastie avec implantation d’une endoprothèse vasculaireRésultats: Amélioration rapide de la fonction rénale à la suite de l’implantation de l’endoprothèse vasculaireEnseignements tirés: Ce cas illustre l’importance d’intégrer les indicateurs cliniques, les informations obtenues à l’échographie et les résultats de laboratoire. L’IRA survenant à la suite d’une greffe hépatique, lorsqu’elle est associée à de l’œdème des membres inférieurs, à des ondes anormalement monophasiques de la veine hépatique à l’échographie Doppler, de même qu’à une faible excrétion urinaire de sodium, devrait évoquer la possibilité d’une sténose de la veine cave inférieure comme facteur étiologique.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Internal Diseases; Nephrology; Health Sciences; PEDİATRİ; Klinik Tıp; Klinik Tıp (MED); ÜROLOJİ VE NEFROLOJİ; PEDIATRICS; CLINICAL MEDICINE; Clinical Medicine (MED); UROLOGY & NEPHROLOGY; Pediatri; Üroloji; Pediatri, Perinatoloji ve Çocuk Sağlığı; Pediatrics; Urology; Pediatrics, Perinatology and Child Health; acute kidney injury; liver transplantation; hepatorenal reflex; venous congestion; Doppler ultrasound; hepatic vein Doppler